2018
DOI: 10.1055/a-0707-6697
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes – Major New Clinically Relevant Aspects

Abstract: The implementation of screening for gestational diabetes (GDM) in the German Prenatal Care guidelines of 2012 and the publication of numerous new studies have led to clinically relevant changes in the care of pregnant women with GDM to whom consideration was given in the new S3 Guideline on the Diagnosis, Management and Follow-up of Gestational Diabetes (AWMF 057/008) published in March this year. Certain aspects are addressed and discussed on the basis of additional background information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…For obese women, it has already been shown that gestational weight gain below the national recommendations for obese mothers (5 – 9 kg) does not adversely affect fetal growth, gestational age at delivery, or mode of delivery 20 . Consequently, recommendations on gestational weight gain have been included in the updated version of the guidelines on the diagnosis, treatment and follow-up of gestational diabetes 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…For obese women, it has already been shown that gestational weight gain below the national recommendations for obese mothers (5 – 9 kg) does not adversely affect fetal growth, gestational age at delivery, or mode of delivery 20 . Consequently, recommendations on gestational weight gain have been included in the updated version of the guidelines on the diagnosis, treatment and follow-up of gestational diabetes 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In principle, however, this should be considered starting at week 37 + 0 of pregnancy, particularly in the case of insulin-dependent diabetes and a foetal weight ≥ 95th percentile. The authors additionally recommend a primary section in the case of an estimated weight of ≥ 4500 g 26 , 27 , 28 . If there is no gestational diabetes, the American College of Obstetricians and Gynecologists recommends a preventive section starting at 5000 g. Induction is not recommended 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Perzentile. Die Autoren empfehlen zudem eine primäre Sectio bei einem geschätzten Gewicht ≥ 4500 g 26 , 27 , 28 . Sofern kein Gestationsdiabetes vorliegt, empfiehlt das American College of Obstetricians and Gynecologists eine präventive Sectio ab 5000 g. Eine Einleitung wird nicht empfohlen 1 .…”
Section: Diskussionunclassified
“…The determination of fetal growth parameters and the use of these fetal growth parameters to guide treatment is an established approach when treating women with gestational diabetes 14 . The current recommendations on managing the treatment of pregnant women with manifest pregestational DM include fetal biometry based on ultrasound examinations carried out every 2 – 4 weeks from the 24th week of gestation (GW) in addition to standard diabetic monitoring of the maternal metabolism 15 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In der Therapie von Frauen mit Gestationsdiabetes ist die Bestimmung der fetalen Wachstumsparameter und die Orientierung der Therapieführung am fetalen Wachstum etabliert 14 . Im Therapiemanagement einer Schwangerschaft mit prägravide manifestem DM werden aktuell ab der 24.…”
Section: Introductionunclassified